Charge-transfer processes and carrier dynamics at the pentacene—C60 interface. (1st February 2019) - Döring, Robin C; Rosemann, Nils W; Huttner, Andrea; Breuer, Tobias; Witte, Gregor; Chatterjee, Sangam
Abstract: Heterostructures of pentacene (PEN) and buckminsterfullerene (C60 ) are frequently attracting scientific interest as a well-defined small-molecule model system for the study of internal interfaces between two organic semiconductors. They are prototypical representatives forming a donor–acceptor combination for studies of fundamental optoelectronic processes in organic photovoltaics. Despite their importance in exciton dissociation, the energetics of their interfacial charge-transfer (CT) states and their microscopic excitation dynamics are not yet clarified and still being discussed. Here, we present steady-state and time-resolved photoluminescence measurements on stacked heterostructures composed of these two materials. All experiments are performed in the visible and near-infrared spectral regions as CT states are expected at energies below the fundamental electronic transitions of the respective bulk materials. A characteristic, interface-specific emission at around 1.13–1.17 eV is found, which we attribute to an interfacial CT state. Its excitation energy dependence reveals the intricate relaxation dynamics of excitons formed in both constituent materials. Moreover, the analysis of the dynamics of the C60 excitons shows that the lifetime of this state is reduced in the presence of an interface with PEN. This quenching is attributed to a long-range interaction, i.e. the relaxation of excitations into the interfacial CT state.